Halal Microcarrier Preparation for Vaccine Manufacturing - A.N. Yusilawati;; M. Maizirwan;; I. Sopyan;; M.S. Hamzah;; K.H. Ng; C.S. Wong (Universiti Sains Islam Malaysia, 2024)
Microcarriers are tiny beads or particles (matrix) with a surface chemistry that facilitates attachment and growth of anchorage-dependent cells in cell culture processes. Tuning the interactions of cells to the engineered matrix is a major challenge in cell and tissue engineering. The aim of this study was to develop polymeric microcarrier to obtain higher cell density in bioreactor culture for vaccine manufacturing from animal cell thus ensuring the whole process is halal. This cell-carrier was developed from micro-size polystyrene beads (100-150µm) which have been surface modified by UV/ozone treatment and covalent immobilization of by gelatin (bovine and fish) on the material surface. Cell loading test in Vero cell culture was performed to evaluate their performance as carrier system. It was found that the system used was effective to develop gelatin coated polystyrene beads having good microscopic and suspension ability, good surface for cell attachment and proliferation, easy sampling and easy cell recovery with highest maximum cell number obtained with no toxicity to the cells. The novelty of this product includes simple and improved technique to prepare halal microcarrier with cheaper production cost. In addition, less concentration of microcarrier (3g/L) can be used for cell culture compared to commercial microcarrier (4g/L - 20g/L). Thus, this matrix can be used to substitute commercial microcarriers which were developed from non-halal resources (porcine gelatin) such as Cytodex 3, FACT III, Collagen from Solo Hill, CGEN 102-L and many more. Therefore, the product is applicable for large scale production and ready for commercialization.